2016
DOI: 10.1128/cvi.00701-15
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of the Effect of Deamidation on the Immunogenicity of Anthrax Protective Antigen

Abstract: The spontaneous modification of proteins, such as deamidation of asparagine residues, can significantly affect the immunogenicity of protein-based vaccines. Using a "genetically deamidated" form of recombinant protective antigen (rPA), we have previously shown that deamidation can decrease the immunogenicity of rPA, the primary component of new-generation anthrax vaccines. In this study, we investigated the biochemical and immunological mechanisms by which deamidation of rPA might decrease the immunogenicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Deamidation of asparagine residues can also significantly affect immunogenicity and efficacy of protein-based vaccines. Specifically, progress to develop next-generation anthrax vaccines has been halted by vaccine instability resulting from asparagine deamidation in anthrax protective antigen 17, 18, 19, 20, 21. Even in the nontherapeutic enzyme glucoamylase, used commercially to produce sweeteners and ethanol, asparagine deamidation causes a decrease in enzyme activity and change in thermodynamic stability 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…Deamidation of asparagine residues can also significantly affect immunogenicity and efficacy of protein-based vaccines. Specifically, progress to develop next-generation anthrax vaccines has been halted by vaccine instability resulting from asparagine deamidation in anthrax protective antigen 17, 18, 19, 20, 21. Even in the nontherapeutic enzyme glucoamylase, used commercially to produce sweeteners and ethanol, asparagine deamidation causes a decrease in enzyme activity and change in thermodynamic stability 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…These results may also suggest a role for receptors on APCs in the presentation of intact surface-localized PA to B cells. With regard to stability, deamidation of asparagine residues in PA was associated with decreased potency, reduced levels of TNAs, and impaired binding of PA to cells (43).…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 , 41 For vaccines, Asn deamidation in critical epitopes of the recombinant protective antigen leads to a change in the conformation of epitopes that causes reduction in potency and immunogenicity of a recombinant anthrax vaccine. 42 , 43 As a part of chemical stability studies, we have identified a glycated B chain species in this lyophilized dmLT formulation by intact MS. The presence of reducing sugars is known to cause glycation in therapeutic proteins by a condensation-type reaction with Lys residues known as the Maillard reaction.…”
Section: Discussionmentioning
confidence: 99%